EXPRESSIVE WRITING AS AN EMOTIONAL REGULATION STRATEGY TO REDUCE FUTURE ANXIETY IN ADOLESCENTS Fathhanah Kemimaro, Rachmawaty M. Noer,, Maselvi Ardhillah Nursyiam, Mira Agusthia - Fathhanah Kemimaro; Rachmawaty M. Neor; Maselvi Ardhillah Nursyiam; Mira Agusthia (Poltekkes Kemenkes Banten, 2026)
Adolescence is a crucial stage of development marked by complex physical, psychological, and social changes. One of the most common psychological issues faced by adolescents is future anxiety, which refers to feelings of fear, worry, and uncertainty about events that have not yet occurred. Academic pressure, career choices, and social expectations are often sources of ongoing anxiety. If not properly addressed, this anxiety can negatively impact mental health, academic performance, and overall quality of life. Expressive writing therapy is a non-pharmacological psychological intervention believed to be effective in helping individuals manage emotions and reduce anxiety levels. This study aimed to determine the effect of expressive writing therapy on reducing future anxiety among adolescents at SMA Al Azhar Batam in 2025. The research used a pre-experimental design with a one-group pretest-posttest approach. A total of 24 students were selected using purposive sampling and participated in two sessions of expressive writing therapy conducted over two consecutive days. The instrument used was the Future Anxiety Scale (FAS). Data were analyzed using the Wilcoxon Signed Ranks Test. All participants experienced a decrease in anxiety scores after the therapy. Statistical analysis showed a significant p-value (p < 0.05), indicating a significant difference between pretest and posttest scores. Expressive writing therapy was proven to have a significant effect in reducing future anxiety in adolescents. This intervention can serve as an alternative psychological approach that is practical, affordable, and applicable in efforts to improve adolescent mental health in school settings.